Financial And Non-Financial Factors As Impacts Of Receiving A Going Concern Audit Opinion - Anjilni, Ratih Qadarti; Musyarofah, Zahroh Al; Rahmawati, Novia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research analysed the effect of Leverage, Audit Tenure and Audit Lag on Going Concern Audit Opinion. The study was conducted on Energy sector companies listed on the Indonesia Stock Exchange in 2019-2023. The methodology used is logistic regression because the dependent variable of this study is a dummy variable. Sample selection was carried out using the purposive sampling method, so that 18 companies were obtained as research samples, and the period studied was 5 years, namely from 2019 to 2023, so that there were 90 samples. The data used were taken from audited financial statements and annual reports issued by each company studied. Hypothesis testing was conducted using the EViews series 12 application. The results of the study indicate that partially Leverage has an effect on Going Concern Audit Opinion, Audit Tenure has no effect on Going Concern Audit Opinion, and Audit Lag has no effect on Going Concern Audit Opinion. Simultaneously, Leverage, Audit Tenure and Audit Lag have an effect on Going Concern Audit Opinion.